Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Berbasis Discovery Learning Untuk Meningkatkan Kemampuan Komunikasi Matematis Peserta Didik - Rini Wahyuni; Kurnia Rahmi Yuberta; Ummul Huda; Elda Herlina (Edusainstika, 2026)
The main problem in this study is the low mathematical communication skills of students; the learning resources do not contain example questions that can improve students' mathematical communication skills. Therefore, it is necessary to have learning resources that can improve students' mathematical communication skills. The learning model used in the Student Worksheet (LKPD) is the Discovery Learning model, because it provides opportunities for students to learn actively and to discover formulas or concepts from the material. The purpose of this study is to produce a Student Worksheet (LKPD) in the form of a Discovery Learning-based model to improve students' mathematical communication skills that are valid, practical, and effective. This study uses a development research method that consists of three stages: define, design, and develop. The instruments used in this study were validation sheets, student response questionnaires, and mathematical problem-solving ability tests. Furthermore, data analysis techniques used to present the research results include validity analysis, practicality analysis, and effectiveness analysis. Based on the results of the study, it shows that the Discovery Learning-based LKPD was designed to be valid, practical, and effective. The validity result of the LKPD was 86% with a very valid category. Meanwhile, the practicality result of the LKPD obtained from the results of the student response questionnaire was 81% with a very practical category. Then, the results of the effectiveness of the Discovery Learning-based LKPD can be seen in the N-gain obtained, which is 0.7. In conclusion, this LKPD is effective in improving students' mathematical communication skills.